Partial recovery after severe immune reconstitution inflammatory syndrome in a multiple sclerosis patient with progressive multifocal leukoencephalopathy. (January 2014) - Calvi, Alberto; De Riz, Milena; Pietroboni, Anna M; Ghezzi, Laura; Maltese, Virginia; Arighi, Andrea; Fumagalli, Giorgio G; Jacini, Francesca; Donelli, Carlotta; Comi, Giancarlo; Galimberti, Daniela; Scarpini, Elio
Progressive multifocal leukoencephalopathy (PML) is a rare and severe complication of natalizumab therapy in patients with multiple sclerosis and it may be accompanied by immune reconstitution inflammatory syndrome (IRIS). Here, we describe a case of abnormally severe IRIS, which occurred 2 months after natalizumab-associated PML in a 38-year-old woman affected by multiple sclerosis. The patient was John Cunningham virus-positive and was treated for 21 months when she developed PML. The subsequent IRIS diffusely afflicted the brain, producing edema and signs of intracranial hypertension, with a clinically severe form compromising the state of consciousness, requiring intensive care and high-dosage steroid treatment. Nevertheless, she survived and partially recovered. There is still difficulty in differentiating PML progression from IRIS onset and there is not a clear description in the literature about different clinical forms of IRIS, prognostic factors and guidelines to properly treat this complication in order to reduce the residual disability of the patient surviving this treatment complication.